Transferring the blues: Depression-associated gut microbiota induces neurobehavioural changes in the rat - Kelly, John R.; Borre, Yuliya; O' Brien, Ciaran; Patterson, Elaine; El Aidy, Sahar; Deane, Jennifer; Kennedy, Paul J.; Beers, Sasja; Scott, Karen; Moloney, Gerard; Hoban, Alan E.; Scott, Lucinda; et al. (Journal of psychiatric research, 2016)
The gut microbiota interacts with the host via neuroimmune, neuroendocrine and neural pathways. These pathways are components of the brain-gut-microbiota axis and preclinical evidence suggests that the microbiota can recruit this bidirectional communication system to modulate brain development, function and behaviour. The pathophysiology of depression involves neuroimmune-neuroendocrine dysregulation. However, the extent to which changes in gut microbiota composition and function mediate the dysregulation of these pathways is unknown. Thirty four patients with major depression and 33 matched healthy controls were recruited. Cytokines, CRP, Salivary Cortisol and plasma Lipopolysaccharide binding protein were determined by ELISA. Plasma tryptophan and kynurenine were determined by HPLC. Fecal samples were collected for 16s rRNA sequencing. A Fecal Microbiota transplantation was prepared from a sub group of depressed patients and controls and transferred by oral gavage to a microbiota-deficient rat model. We demonstrate that depression is associated with decreased gut microbiota richness and diversity. Fecal microbiota transplantation from depressed patients to microbiota-depleted rats can induce behavioural and physiological features characteristic of depression in the recipient animals, including anhedonia and anxiety-like behaviours, as well as alterations in tryptophan metabolism. This suggests that the gut microbiota may play a causal role in the development of features of depression and may provide a tractable target in the treatment and prevention of this disorder.